SUPERCONNECTOR : STOP NETWORKING AND START BUILDING BUSINESS RELATIONSHIPS THAT MATTER - Gerber, Scott, 1983-
The authors promote a new category of professionals born out of the social media era: highly valuable community-builders who make things happen through their keen understanding and utilization of social capital. Superconnectors understand the power of